2016
DOI: 10.1002/jaal.556
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Hypothetical Adolescent in Evaluating and Teaching Young Adult Literature

Abstract: Evaluating young adult literature on behalf of hypothetical adolescent readers may naturalize a series of myths about who adolescents are, what they care about, and what they are capable of.W ould adolescents choose to read this book? What problems or issues could I address with this book? Would adolescents see these issues as relevant? These are questions that English language arts (ELA) teachers often ask themselves when evaluating young adult literature (YAL), defined in this article as literature marketed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The youth adaptation of Dreamland, therefore, positions youth as needing simplicity, protection, and a sense of optimism. This finding resonates with previous scholarship suggesting youth are often imagined reductively as readers and thinkers, as if they are a monolithic group with a preditable set of characteristics, thoughts, and needs (Lesko, Simmons, Uva, 2020;Sarigianides, Petrone, & Lewis, 2017;Sulzer & Thein, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…The youth adaptation of Dreamland, therefore, positions youth as needing simplicity, protection, and a sense of optimism. This finding resonates with previous scholarship suggesting youth are often imagined reductively as readers and thinkers, as if they are a monolithic group with a preditable set of characteristics, thoughts, and needs (Lesko, Simmons, Uva, 2020;Sarigianides, Petrone, & Lewis, 2017;Sulzer & Thein, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Other scholars have used Lesko’s work to think critically about teaching and learning in ELA. Sulzer and Thein (2016) examined 13 pre-service teachers (PST) in a YAL course and found that “monolithic stances toward youths, while deeply embedded in the fabric of Western culture, are not simply something that preservice teachers bring to their readings of YAL.” Such stances may be unintentionally fostered by “a familiar style of questioning often used to evaluate YAL” (p. 168), which can lead to monolithic and deficit thinking. Researchers have also pointed to connections between teacher thinking and curricular decisions.…”
Section: Constructing Adolescentsmentioning
confidence: 99%
“…Research shows that many PSTs hold these same preconceived notions of youth readers: that youth fit a decontextualized, universal definition and are all the same; that they need protecting from harsh realities; and that they are incapable of having critical and productive conversations about issues of social justice (Gay and Kirkland, 2003;James, 2008;Petrone and Sarigianides, 2017;Sulzer and Thein, 2016). Given the tensions surrounding these same important topics in the adult world at large, it is not surprising that PSTs would presume incompetence in young people's enactment of democratic discussions around issues of social justice.…”
Section: Perceptions Of Youthmentioning
confidence: 99%